Back Cover: Electrochromism of Nanographenes in the Near‐Infrared Region (Angew. Chem. Int. Ed. 17/2022). Issue 17 (28th March 2022) - Matsumoto, Ikuya; Sekiya, Ryo; Fukui, Hiroji; Sun, Ren‐De; Haino, Takeharu
Abstract : Electrochromism of functionalized nanographenes is reported by Ryo Sekiya, Takeharu Haino, and co‐workers in their Communication (e202200291) . The electrochromic behavior reached from the visible to the near‐infrared region over 2000 nm. The transmittance of the light in the NIR region displayed a 50–60 % change upon redox treatment.